Peru-Chile: Post War Syndrome - Nizama Valladolid, Martin (2009)
In regard to the espionage committed by Chile against Peru between 2004 and 2009, this article examines some characteristics of the militarism, the arms race and geopolitical expansion of Chile, after the Pacific War (1879) that separated from Peru and Bolivia the provinces of Antofagasta, Tarapacá and Arica. Henceforth, the history between Chile and Peru, was developed based on a dichotomous victor-vanquished relationship in which prevails attitudes of pride, arrogance, threats and unbridled arms race, hostility and warmongering, militarism fueled by the greedy Pinochetist military caste that still exert a masked tutelage on the Chilean democracy, and on the other hand, resentment, mistrust and fear present among Peruvians. This reality has become a highlight in the discovery of a spy ring against Peru paid by Chile, having engaged the services of a peruvian military officer in service for the purpose. This dysfunction in bilateral relations over 130 years, has generated a post war syndrome in which the winner of military confrontation feels superior to the vanquished who is underestimated and considered substantially lower, establishing an unresolved relationship based on envy aggression versus resentment fear, which feeds the expansionist plans of Chile, primarily in the economic, trade or business field, and thereafter militarily, for which they arm themselves. Following the conclusion, some alternatives are suggested for dealing with the post-war syndrome.